Women’s Motivations for Becoming a Police Officer: A Chinese Case Study on Women in Policing - Shen, Anqi (Women & criminal justice, 2024)
This article presents a qualitative study that examines the reasons why women want to be a police officer in the mainland of the People’s Republic of China. It aims to explore females’ entry into the police organization, policewomen’s occupational roles and positions, the perceived nature of policing and, to a lesser extent, local police culture. The article argues that China does not need a creative strategy to attract females to join the police. Instead, if structural changes are not possible for now, it needs to change mindset, to scrap the quota that restricts women’s entry and allow female officers more choices and to be more actively engaged in mainstream policing if they so wish. Through the case study, the article accentuates variations in different social environments in comparative criminal justice studies and gender policing in particular. It thus also promotes Southern criminology and Southern Theory for contributions to knowledge production.